IMPLEMENTATION OF CROSS-MINISTRY AND INSTITUTIONAL COOPERATION ON THE ERADICATION OF CORRUPTION IN INDONESIA IN THE FRAMEWORK OF UNCATOC & UNCAC AND ITS RELATIONSHIP WITH THE IMMIGRATION LAW - Rafsanjani Is Marus; Wahyu Eka Putra (Journal of Law and Border Protection, 2020)
The international community, including Indonesia, agrees that corruption is a serious crime that can be transnational, therefore cooperation between countries is needed. Cooperation can be done bilaterally, regionally or multilaterally. Cooperation will be more solid if these countries have the same commitment to eradicating corruption, one of which is realized by ratifying UNCATOC & UNCAC, then harmonizing the laws and regulations in their countries so that they can implement the anti-corruption guidelines properly. Immigration has become one of the fulcrums of national interests. The form of coordination and cooperation with DITJENIM is often carried out by certain ministries or agencies in the event that the perpetrator of the corruption crime has fled abroad through the track record of crossing in the immigration database. This research uses a statute approach and a conceptual approach. This study found that the handling of corruption cases must pay attention to quality and be able to provide a deterrence effect. There are various provisions, then a collective agreement is made to strengthen cohesiveness and togetherness in the eradication of corruption, which in turn will have a positive impact in optimizing the eradication of corruption in Indonesia.